Multisensor Fire Detection System Mobile Robot as a Learning Media in Firefighting Robotic Course - Direstu Amalia; Wildan Nugraha; Sunardi Sunardi; Rio Rizko; Jhellyananda Putri; Randa Agusta Pratama (Journal of Innovation in Educational and Cultural Research, 2023)
Firefighting Robotic technology has been used for a long time to achieve aviation safety and security goals. The research is deemed necessary because of some related issues: 1) A pressing need for lecturers and students to have access to learning media; 2) A lack of practical media that are pertinent to industries needs; and 3) Practical learning of Firefighting Robotics necessitates learning media that are by the needs of cadets. This research aims to create an innovative learning media for a firefighting robot course based on the Internet of Things (IoT) with a Proportional-Integrative-Derivative (PID) control system using a multisensor according to learning outcomes. The research method used the Plomp Model with initial data collection techniques using literature study and observations of Firefighting Robot designs and course outcomes. The research results are an automatic fire extinguishing Firefighting Robot that works in a labyrinth with a web-based main control system as a server connected to the client, namely the Firefighting Robot and fire alarm. The PID control system test result is Kp = 100, Kd = 100, and Ki = 10, which makes it stable in maneuvering the labyrinth. Validation results from material and media experts were conducted, and the learning media application successfully carried out system instructions. The material experts resulted in a quality aspect of the material content score of 4.8 with the category "Very Good". As a prototype, the researchers hope the firefighting robot concept can be developed on a large scale to support firefighting activities in real field situations in further research.